History of Chronic Energy Deficiency (CED) during Pregnancy and the Incidence of Stunting among Children Aged 0-59 Months in East Jakarta - Hesty Ayu Nurranti Ramadhani; Sudarto Ronoatmodjo (Poltekkes Kemenkes Palu, 2023)
Based on SSGI data (2021), the prevalence of stunting among under-five children in DKI Jakarta Province was 16.8%. Meanwhile, based on the Ministry of Health Republic of Indonesia Performance Report for 2021, there were 3.1% of pregnant women with Chronic Energy Deficiency (CED) in DKI Jakarta Province. This study aims to determine the correlation between a history of Chronic Energy Deficiency (CED) during pregnancy and the incidence of stunting among children aged 0-59 months in East Jakarta. This study involved secondary data derived from the e-PPGBM application for the City of East Jakarta in 2021 with a sample size of 2,688 people and data were analyzed using Cox-regression. Based on the results of data analysis, it was found that the proportion of pregnant women with a history of CED was 3.7% and the proportion of under-five children with stunting was 21.1%. The multivariate analysis on the correlation between a history of CED during pregnancy and the incidence of stunting after being controlled by the potential confounder variable obtained a PR of 1.354 (95% CI: 0.922-1.988). It can be concluded that there was no significant correlation between a history of CED during pregnancy and the incidence of stunting in the East Jakarta area in 2021 after being controlled by the potential confounder variable. However, there are still possible confounder factors that should be analyzed further.